ASSA13-03-6 Effects of Renal Sympathetic Denervation on the Development of Atrial Fibrillation Substrates in Dogs with Pacing-Induced Heart Failure. (29th April 2013) - Zhao, Qingyan; Yu, Shengbo; Xiao, Jinping; Dai, Zixuan; Wang, Xule; Huang, Congxin
Abstract : Objective: We examined the role of renal denervation on the inducibility of AF in dogs with pacing-induced HF. Background: Atrial fibrillation (AF) and heart failure (HF) are common interrelated conditions that are associated with renin-angiotensin-aldosterone system activity. Methods and Results: Nineteen dogs were randomised into sham-operated (7 dogs), HF (6 dogs) and HF+renal artery ablation (RAA, 6 dogs) groups. Sham-operated dogs were implanted with transvenous cardiac pacemakers without pacing. Dogs in the HF group were implanted with pacemakers and underwent right ventricular pacing for 3 weeks at 240 bpm to induce HF. The dogs in the HF+RAA group received double renal artery ablation. The dogs recovered for 8 weeks and underwent the same HF-inducing procedure. Compared to the baseline, the atrial dimensions increased and the right atrial ERP (131 ± 14 ms to 112 ± 12 ms, p = 0.02) decreased significantly after 3 weeks in the HF dogs but not the HF+RAA dogs. A greater number of AFs were induced in the HF dogs than the HF+RAA dogs (2.2 ± 0.6 vs. 0.3 ± 0.3, p = 0.03). The atrium from HF hearts revealed a large amount of fibrosis, whereas control and HF+RAA dogs showed minimal fibrous tissue. The levels of BNP, Ang II, TNF-α and expression of TGF-β and Cx43 in atrial tissue were increased in the HF dogs compared to the sham-operated and HF+RAA dogs. Conclusion: RAA suppressed the atrial substrate remodelling and the AF vulnerability that was induced by long-term rapid ventricular pacing.